Exclusive Breastfeeding and Low Birth Weight Factors on the Incidence of Stunting in Toddlers at the Posyandu in the Penkase Oeleta Health Center Area - Servasia Yosefina Mones (IRDH International Journal of Technology, Agriculture and Natural Sciences, 2026)
Stunting is a chronic nutritional problem in toddlers that affects a child's growth and development. This study aims to analyze the relationship between exclusive breastfeeding and low birth weight (LBW) with the incidence of stunting in toddlers aged 24–60 months at the Integrated Health Post (Posyandu) in the Penkase Oeleta Health Center area. This study used an analytical design with a cross-sectional approach. The sample consisted of 30 toddlers selected using accidental sampling techniques. Data were collected through interviews with the toddlers' mothers and measurements of the toddlers' height, and then analyzed using the Chi-Square test. The results of the study showed a significant relationship between exclusive breastfeeding and the incidence of stunting (p=0.02), as well as between LBW and the incidence of stunting (p=0.00). Toddlers who do not receive exclusive breastfeeding and have a history of low birth weight tend to be at a higher risk of stunting compared to toddlers who receive exclusive breastfeeding and are born with normal birth weight. This study concludes that exclusive breastfeeding and low birth weight are factors associated with the occurrence of stunting in toddlers aged 24–60 months at the Posyandu under the Penkase Oeleta Health Center, thus requiring promotive and preventive efforts through nutrition education and continuous monitoring of maternal and child health.